Factors Associated with Transport Instability and Outcome Deterioration During Interhospital Intensive Care Transfers of Patients with COVID-19 in Germany - Leonie Hannappel; Jan Wnent; Rolf Lefering; Janina Bathe; Jan-Thorsten Gräsner (Journal of Clinical Medicine, 2026)
Background/Objectives: The COVID-19 pandemic created demand for interhospital transfers of critically ill patients to balance intensive care capacity. Evidence on the logistics and immediate physiological outcomes of such transfers in Germany remains limited. Methods: This multicenter retrospective observational cohort study included 414 interhospital intensive care transport records of adults with COVID-19 in Germany between January 2020 and June 2021. Logistic regression assessed factors associated with transport instability and deterioration, and linear regression assessed factors associated with transfer-phase duration. Results: Transport modality was incompletely documented; 404 records documented ground-based intensive care transport by intensive care transport vehicle (ITW) and 10 by fixed-wing transport. Respiratory support was frequently documented, with intubation recorded in 71.3% of transports, catecholamines in 64.1%, and ECMO transport in 7.2%. Mean takeover, transport, and handover times were 53, 59, and 64 min, respectively. At least one clinically relevant threshold-crossing event during transport was documented in 43.9% of records, while 15.9% met the study-specific definition of transport instability requiring at least two separate threshold-crossing events. Outcome deterioration occurred in 16.4%. In the multivariable analyses, serious impairment of physiology was associated with transport instability, while instability during transport was strongly associated with deterioration at handover. Conclusions: Physiological instability and immediate deterioration were frequent in this selected multicenter cohort. Because documentation was heterogeneous, providers participated voluntarily, and longer-term outcomes were unavailable, the findings should not be interpreted as establishing transport-related causation or overall transport safety.